Towards a good governance system : The implementation of a system of management control in a public institution: Case of a Regional Academy for Education and Training. (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2016)
The issue of reforming the Moroccan educational system has become an important national topic. The government is looking forward to achieve the objectives that have been defined forward for this system and contribute to let it be performant.Effectively, the Moroccan educational system is the second national priority. All the national speeches of his majesty king of Morocco are focalized in reorganizing this system by detecting the problems and developing pertinent solutions and tools able to make the difference in the future. The Moroccan context is characterized by the will of government to establish the notion of governance and performance in the public services in general and in the national educational system especially. The aim of our paper is to study how can we introduce the concept of performance in the educational system by integrating a system of management control in the system of education? The hypothesis that the three habitual summits of management control namely- means objectives and realizations arenot enough for studying the complexity and the missions of such a sector like the educational system where the satisfactions of users is an important factor that must be took into consideration.